2016
DOI: 10.1242/dev.139022
|View full text |Cite
|
Sign up to set email alerts
|

ATR maintains chromosomal integrity during postnatal cerebellar neurogenesis and is required for medulloblastoma formation

Abstract: Microcephaly and medulloblastoma may both result from mutations that compromise genomic stability. We report that ATR, which is mutated in the microcephalic disorder Seckel syndrome, sustains cerebellar growth by maintaining chromosomal integrity during postnatal neurogenesis. Atr deletion in cerebellar granule neuron progenitors (CGNPs) induced proliferation-associated DNA damage, p53 activation, apoptosis and cerebellar hypoplasia in mice. Co-deletions of either p53 or Bax and Bak prevented apoptosis in Atr-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 68 publications
0
52
0
Order By: Relevance
“…Our group has found that Atr deletion in CGNPs causes chromosomal damage and widespread apoptosis but no defect in proliferation at the early postnatal stage, when CGNP proliferation is maximal [134] . Cerebellar hypoplasia was partially rescued by co-deletion of either Bax and Bak or p53 .…”
Section: Atr Is Mutated In Seckel Syndrome and Plays An Important mentioning
confidence: 99%
See 3 more Smart Citations
“…Our group has found that Atr deletion in CGNPs causes chromosomal damage and widespread apoptosis but no defect in proliferation at the early postnatal stage, when CGNP proliferation is maximal [134] . Cerebellar hypoplasia was partially rescued by co-deletion of either Bax and Bak or p53 .…”
Section: Atr Is Mutated In Seckel Syndrome and Plays An Important mentioning
confidence: 99%
“…We have found that Atr deletion in two different mouse models of medulloblastoma either significantly reduced tumorigenesis or completely abrogated tumor formation [145] . Our group is currently testing pharmacological ATR inhibition in mice with established medulloblastoma using a novel formulation in which the small molecule ATR inhibitor VE-822 is packaged in polymeric micelle nanoparticles (pVE-822).…”
Section: Atr Is Mutated In Seckel Syndrome and Plays An Important mentioning
confidence: 99%
See 2 more Smart Citations
“…22, 23). MBs were widely accepted to occur due to the transformation of CGNPs (24). We next cultured CGNPs isolated from neonatal mice, and achieved siRNA-based knockdown of Nkx2-2as in these cells (Fig.…”
Section: Resultsmentioning
confidence: 99%